2013
DOI: 10.1007/s10103-013-1321-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Er:YAG and Er,Cr:YSGG laser irradiation on the adhesion to eroded dentin

Abstract: Limited information is available regarding the adhesion to eroded dentin. This study aims to evaluate the effect of different surface treatments on eroded dentin morphology and on microtensile bond strength (μTBS) of adhesive systems to this substrate. Ninety-six extracted third molars were randomly divided into eight groups (n = 12) according to the type of surface treatment and the adhesive system: G1 = Control + Clearfil SE Bond [SE], G2 = Diamond bur [DB] + SE, G3 = Er:YAG laser (60 mJ, 2 Hz, 0.12 W, 19.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 40 publications
3
22
0
18
Order By: Relevance
“…It infers a good reliability of the present µTBS test conditions and correlates well with the literature for eroded dentin bonded to adhesive systems 20,[30][31][32] . On the other hand, eroded dentin restored with ionomer based materials usually shows higher incidence of cohesive and mixed failure 22 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It infers a good reliability of the present µTBS test conditions and correlates well with the literature for eroded dentin bonded to adhesive systems 20,[30][31][32] . On the other hand, eroded dentin restored with ionomer based materials usually shows higher incidence of cohesive and mixed failure 22 .…”
Section: Discussionsupporting
confidence: 72%
“…The intense micromechanical interlocking produced by phosphoric acid etching might explain the higher bond strength observed to the Adper Single Bond 2. Contradictory results 30 found better results for self-etch approach when compared to etch-and-rinse bond strength results, which infers that the bonding effectiveness to eroded dentin might be product-dependent. Forgerini et al 21 (2017) reported that the use of an universal adhesive did not provide the same bonding efficacy on eroded dentin as on sound dentin, irrespective of the etching mode.…”
Section: Discussionmentioning
confidence: 98%
“…The water molecules among the hydroxyapatite crystals absorb the beams and evaporate; as a result, the internal pressure increases and microexplosions occur leading to substrate ejection and microstructural alterations. 25,28,29 Although several studies have assessed the effects of erbium family lasers on bleached enamel, 3,[30][31][32] to the best of our knowledge no study has compared the effects of Er:YAG and Er,Cr:YSGG lasers on bleached dentin. Based on our results, Er:YAG laser irradiation led to significantly higher bond strength compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…28,32,33 Finally, reduction in microbial count due to erbium laser irradiation may also explain the higher bond strength values. 25,[34][35][36][37] Although Er,Cr:YSGG laser treatment caused an increase in bond strength compared to the control group, the amount was insignificant. The drop in shear bond strength values in the Er,Cr:YSGG group compared to the Er:YAG group may be due to the difference in the morphology of the lased dentin surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation